Association of real life postural transitions kinematics with fatigue in neurodegenerative and immune diseases - Robbin Romijnders; Arash Atrsaei; Rana Zia Ur Rehman; Lea Strehlow; Jèrôme Massoud; Chloe Hinchliffe; Victoria Macrae; Kirsten Emmert; Ralf Reilmann; C. Janneke van der Woude; Geert Van Gassen; Frédéric Baribaud; et al. (npj Digital Medicine)
Abstract Fatigue is prevalent in immune-mediated inflammatory and neurodegenerative diseases, yet its assessment relies largely on patient-reported outcomes, which capture perception but not fluctuations over time. Wearable sensors, like inertial measurement units (IMUs), offer a way to monitor daily activities and evaluate functional capacity. This study investigates the relationship between sit-to-stand and stand-to-sit transitions and self-reported physical and mental fatigue in participants with Parkinson’s, Huntington’s, rheumatoid arthritis, systemic lupus erythematosus, primary Sjögren’s syndrome and inflammatory bowel disease. Over 4 weeks, participants wore an IMU and reported fatigue levels four times daily. Using mixed-effects models, associations were identified between fatigue and specific kinematic features, such as 5th and 95th percentiles of sit-to-stand performance, suggesting that fatigue alters the control and effort of movement. These kinematic features show promise as indicators for fatigue in these patient populations.